The microphysical pathway to contrail formation. Issue 15 (13th August 2015) - Kärcher, B.; Burkhardt, U.; Bier, A.; Bock, L.; Ford, I. J.
Abstract A conceptual framework to predict microphysical and optical properties of contrail particles within a wingspan behind the source aircraft is developed. Results from two decades of contrail observations and numerical simulations are reviewed forming the basis of theoretical model development. The model utilizes cloud theory applied to the dynamics and thermodynamics of jet aircraft exhaust plumes in upper tropospheric conditions. Droplet nuclei include soot particles emitted from aircraft engines and atmospheric particles entrained into the plume. These precursor particles activate into copious homogeneously freezing water droplets as the plume relative humidity rises beyond liquid water saturation. A unimodal size spectrum of ice particles develops wherein ice particles grow to micrometer mean sizes. Contrail particle formation is analyzed over a wide range of soot emissions relating to conventional jet fuels as well as to alternative aviation fuels producing much less soot and volatile particle emissions. For current aviation fuels and propulsion technology, the number of contrail ice particles scales roughly in proportion to the number of emitted soot particles that act as water condensation nuclei despite their poor hygroscopicity. Close to the contrail formation threshold, only few plume particles can be water activated and freeze. Implications for effects of alternative fuels on contrails, an arena for future scientific exploration, are outlined.